Islamic Education as Cultural Resilience: Malay Identity amid Religious Pluralism in Southern Thailand - Umeirsyah Umeirsyah; Rosidin Rosidin; Siti Mutholingah; Mahammadaree Waeno (Abjadia : International Journal of Education, 2026)
This study examines the crucial role of Islamic education for the Malay community in Pattani, Southern Thailand, in safeguarding cultural identity amid the challenges of religious pluralism and national assimilation policies in daily practices. The study employs a qualitative approach with an interpretive case study design, collecting data through participatory observation, in-depth interviews and document analysis. The findings reveal that the dynamics of Islamic education are characterized by the implementation of a dual curriculum that combines the national curriculum with religious content, generating identity tensions among Muslim students. Cultural preservation is effectively carried out through traditional educational institutions such as pondok pesantren (Islamic boarding school) and “Malay schools,” which instill Malay values and use the local language as the medium of instruction. In addition, the values of multiculturalism and tolerance are deeply embedded in the learning process, for example, even though Santiwitya is an Islamic school, the curriculum still adapts the national compulsory curriculum in the form of general subjects which include examples of teachings from Buddhism. The novelty of this research lies in its holistic approach because this approach viewing Islamic education not only as a fortress of cultural preservation but also as an active agent in cultivating tolerance and serving as a bridge for dialogue. Theoretically, the study demonstrates that strong religiosity can coexist with inclusive attitudes, while practically it offers a model of community-based education as an effective strategy for cultural reconciliation and the preservation of minority identities.